2005
DOI: 10.1103/physrevb.72.075137
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature dephasing saturation from elastic magnetic spin disorder and interactions

Abstract: We treat the question of the low temperature behavior of the dephasing rate of the electrons in the presence of elastic spin disorder scattering and interactions. In the frame of a self-consistent diagrammatic treatment, we obtain saturation of the dephasing rate in the limit of low temperature for magnetic scattering, in agreement with the non-interacting case. The magnitude of the dephasing rate is set by the strength of the magnetic scattering rate. We discuss the agreement of our results with relevant expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The combination (Dq 2 + r) in V (q, ω) is considered here for the first time. The factor Dq 2 indicates disorder induced diffusion of the quasi-particles, with diffusion coefficient D [14,21]. This factor could also originate from antiferromagnetic damping, but this origin would not be consistent with our treatment of ferromagnetic fluctuations -cf.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The combination (Dq 2 + r) in V (q, ω) is considered here for the first time. The factor Dq 2 indicates disorder induced diffusion of the quasi-particles, with diffusion coefficient D [14,21]. This factor could also originate from antiferromagnetic damping, but this origin would not be consistent with our treatment of ferromagnetic fluctuations -cf.…”
mentioning
confidence: 74%
“…below. The factor r may originate from the inadvertent presence of elastic magnetic impurities in the samples [21], and should be equal to the relevant scattering rate τ −1 S . It can also originate from the fermiology of a clean system (without disorder).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H, as in the systems of interest mentioned below, like a = h s , h = |H/H c − 1|, s > 0, where H c is the critical field. The factor Dq 2 indicates disorder induced diffusion of the quasiparticles, with diffusion coefficient D 14,17 . For the purpose of our calculations, we will treat ξ and a as independent parameters.…”
Section: The Modelmentioning
confidence: 99%
“…Among the current opinions on the matter, it has been suggested that the saturated value should depend on the specific sample geometry, 9 the level of disorder in the sample, 10 the microscopic qualities of the defects, 11,12 or e-e scattering mediated by the magnetic exchange interaction. 13 Others argue that the saturation is caused by extrinsic mechanisms, such as magnetic impurities 14 and magnetic spin-spin scattering, 15 hot electron effects, 16 electromagnetic noise sources, 3 or non-equilibrium effects. 17 The possible extrinsic mechanisms urge caution when determining the actual temperature of the twodimensional electron system and ensuring low external radiation is small.…”
Section: Introductionmentioning
confidence: 99%